The origins and functions of Islamic domestic courtyards - Spahic, Omer (IIUM, 2008)
This book discusses the phenomenon of the courtyard in Islamic domestic architecture, focusing on the issues of its origins and diverse functions. The book treats the phenomenon of Islamic domestic courtyards as a cultural, environmental, structural and, above all, religious one, because it is the message of Islam that presided, by and large, over the inception and proliferation of what later became known as the Islamic domestic courtyard. Indeed, there were many other factors at play, however, Islam with the hierarchy of its standards and morals was the most important force that furnished the Islamic domestic courtyard with both its essence and identity, rendering the many indigenous geographical, climatic, cultural and other inherited factors and features rather ancillary, albeit without intending to diminish or downplay the latter’s position and importance. The book is divided into seven chapters. Since the domestic courtyard is fundamental to the remarkable societal stature of the house, it was but appropriate to start the book with a chapter containing some general substance on the relationship between spirituality and the house in Islam. Next, two chapters on the origins of the phenomenon of the domestic courtyard, in general, and the Islamic domestic courtyard, in particular, follow, namely “Domestic Courtyards before Prophet Muhammad (pbuh)” and “The Advent of Islam and Domestic Courtyards”. This is followed by four chapters concerning the idea of the functions of Islamic domestic courtyards. The themes discussed therein are related to the climate, environment, privacy and recreation factors. The four chapters attempt to illustrate the extent of the impact which those factors have on the functions of Islamic domestic courtyards while operating within the ideological frameworks of the Islamic worldview and its systems of living. On the whole, the subject of Islamic domestic courtyards is an extremely important one. This is so because the role and functions of the courtyard are central to the role and functions of the house phenomenon, which, in turn, serves as a framework for the actualization of the family institution without which the fulfillment of the divine purpose on earth becomes impossible. Obviously, this is not a book written from a sheer perspective of architecture. It follows that discussing the plans and structural designs of Islamic domestic courtyards is not the primary focus in the book. Under its long-term Research Grant Scheme, the Research Center of the International Islamic University Malaysia sponsored enthusiastically a research project the output of which is this book. My profound gratitude is therefore extended to the Center and the University. My special thanks are also due to the leadership of the Kulliyyah of Architecture and Environmental Design for its unreserved support I enjoyed in the course of my research engagements. The research that resulted in writing this book was partly library based. However, due to the nature of the theme, several research field trips to some centers of Islamic culture were essential for the successful completion of the project. Thus, the following cities were visited: Marrakech and Fez in Morocco, Lahore in Pakistan, San’a in Yemen, Cairo in Egypt and Istanbul in Turkey. For obtaining the data during the research field trips, the following methods were used: observation, surveillance, taking photographs and interviews. While researching the topic in Lahore, the kindness and help of Assoc. Prof. Dr. Ajaz Anwar, from Lahore’s National College of Arts, were indispensable, for which I feel very much indebted. While in Morocco, I was fortunate to enjoy the noble hospitality of the Abisourour family. Of them, however, the unreserved help and guidance of Mr. Mustafa and his wonderful family in Marrakech are to be singled out here. The help and support of Mr. Zohayr in Fez were very crucial as well, making my stay there a wonderful experience. I pray to Almighty Allah to grant all the persons mentioned every good of this world and the Hereafter. Moreover, Mr. Dilmi Jamel, from Algeria and a Master’s student at the Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, furnished me with some information about domestic courtyards in Algeria. Also, Mr. Faris Gorashi, from Sudan and a PhD student at the Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, furnished me with some information about domestic courtyards in Sudan. Mr. Muhammad Waseem Akhtar from Lahore, Pakistan, was kind enough to provide me with some information on domestic courtyards in Lahore’s rural areas. My profound gratitude is thus extended to all of them. A majority of data needed for the pure theoretical part were found in the compilations of authentic hadiths (the Prophet Muhammad’s tradition) and their commentaries, in the books of sirah (chronicles of Prophet Muhammad’s life), in chronicles with general content, in relevant books on cities, geography, architecture, and on medieval travels, and, last but not least, in the Holy Qur’an and its various commentaries (tafsir). A number of contemporary books dealing with a variety of religious, social and built environment issues, written by both Muslims and non-Muslims, have also been used. Finally, I welcome any constructive and academic suggestion concerning the book’s contents, such as my methodology, arguments, inferences, and the nature of the collected data and my understanding and interpretation of them.